Musculus Palmaris Longus: Influence on Playing Capability of Keyboard Musicians – Preliminary Report - Dąbrowski, Krzysztof; Stankiewicz-Jóźwicka, Hanna; Kowalczyk, Arkadiusz; Markuszewski, Michał; Ciszek, Bogdan (Frontiers in Psychology, 2018)
Musculus Palmaris Longus is one of the most variable anatomical structures in the human body. Despite being biomechanically active, it is vastly considered to have no impact on the functionality of the upper extremity in the general population. The aim of this study is to examine the relation between playing capability of young musicians and morphology of Musculus Palmaris Longus and to compare it with the relation between manual capability of non-musicians and morphology of their Musculus Palmaris Longus. 42 forearms of 21 healthy individuals (11 musicians and 10 non-musicians) were subjected to Shaeffer’s test and ultrasound imaging and tested by dynamometer for hand grip strength and the first and fifth finger opposition before and after exertion. No difference in morphology pattern was observed between the groups. In the musicians, a substantial loss of a hand grip strength of the left hand compared to the right hand after exertion, regardless of lateralization, was observed. A disproportion in exhaustion of the musician’s hands with unilateral absence of Palmaris Longus was observed – the difference in grip strength between the dominant and non-dominant hand before and after exertion increased over eight times more than in the musicians with bilateral presence. There is no difference in Palmaris Longus morphology between either the musicians or non-musicians. Regardless of lateralization, the musician's left hand in musicians seems weaker and therefore more prone to misuse related injuries. Palmaris Longus may play a role in musicians in balancing muscular exhaustion.